Sharirik Braddhi Evam Vikas: - (Journal of Advances and Scholarly Researches in Allied Education, 2012)
^^'kkjhfjd f'k{kk fo|k dk og Hkkx gS tks O;fDr ds laiw.kZ O;fDrRo dkfodkl ,oa izf’k{k.k 'kkjhfjd xfrfof/k;ksa ds }kjk djsA**        &,-vkj- oseSu